MaxEnt model-based prediction of potential suitable habitats of three Trichosanthes L. species in China under future climate change scenarios - Wang, Xiaomeng; Ding, Yuanyuan; Duan, Chunfeng; Xu, Yunchuan; Zhang, Chen; Wang, Zihan (Frontiers in Plant Science, 2026)
IntroductionGlobal warming is reshaping species’ distributions, threatening the habitats of three medicinal lianas in the genus Trichosanthes, and highlighting the need to predict their potential suitable areas under future climate conditions. This study focuses on Trichosanthes rubriflos, Trichosanthes rosthornii, and Trichosanthes kirilowii (T. rubriflos, T. rosthornii, and T. kirilowii), aiming to understand how climate change will affect their distributions and which climatic drivers primarily influence their habitat suitability.MethodsPresent and future suitability patterns were delineated using an optimized MaxEnt model, driven by contemporary climate data and four Shared Socioeconomic Pathway (SSP) scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP5-8.5). Model performance was enhanced through parameter tuning and evaluation, and the principal climatic drivers of habitat suitability were identified from the fitted models.ResultsThe tuned MaxEnt models reliably predicted habitat suitability. T. rubriflos showed largely contiguous suitability across the low-mountain and hilly belts of South and Southwest China. T. rosthornii was concentrated along the eastern Loess Plateau and the mountains of North China, while T. kirilowii exhibited a patchy distribution across the middle-lower Yangtze region. Temperature seasonality emerged as the primary driver for T. rubriflos, while annual precipitation was the most influential factor for T. rosthornii and T. kirilowii. Across all scenarios, habitat expansions generally outpaced contractions, with species shifting poleward and upslope. Scenario-specific responses included the expansion of T. rubriflos in South China and the northward movement of T. rosthornii under SSP3-7.0, as well as the expansion of T. kirilowii into southwestern mountain systems, coupled with partial contraction on the North China Plain under SSP5-8.5.DiscussionDistributions of the three Trichosanthes species are chiefly shaped by temperature seasonality (TS) and annual precipitation (AP), with species-specific sensitivities: TS dominates T. rubriflos, AP (plus cold stress) constrains T. rosthornii, and T. kirilowii shows mid-range (double-threshold) responses. Across 2061–2080, ranges generally expand and shift poleward and upslope; suitability peaks under SSP3-7.0 for T. rubriflos and T. rosthornii, and under SSP5-8.5 for T. kirilowii.These findings provide a scientific basis for identifying future conservation priorities, guiding in situ protection in persistent or newly suitable regions, and informing climate-adaptive management of medicinal Trichosanthes species.